Vocabulary Growth Through Immersive App-Based Learning: A Study of Duolingo and Quizlet - Vivi Amanda; Yesi Darmayanti; Rani Zahra; Arrohman Arrohman; Tina Angriani Lubis (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Vocabulary mastery is a fundamental component of English proficiency, yet many EFL learners continue to struggle with vocabulary retention and contextual use despite traditional instruction. The integration of mobile-assisted learning applications offers new opportunities to enhance engagement and autonomy; however, a gap remains between theoretical expectations of mobile learning effectiveness and its actual implementation in classroom contexts. Therefore, it aims to explore how immersive app-based learning through Duolingo and Quizlet supports vocabulary growth among higher education students. Employing a qualitative descriptive design, the study involved first semester students of English Study Program. Data were collected through semi-structured interviews and document analysis. The data analyzed using thematic analysis supported by triangulation for validity. The findings revealed four dominant themes: (1) students’ learning profile using Duolingo and Quizlet (2) improved vocabulary retention and contextual application facilitated by spaced repetition and retrieval practice; (3) heightened motivation and engagement through gamified features; (4) development of self-regulated learning behaviors such as goal-setting and progress monitoring; and (5) the crucial role of lecturer mediation and contextual factors in enhancing app effectiveness. The study concludes that immersive app-based learning significantly enhances vocabulary acquisition when technological features are supported by motivational design, learner autonomy, and instructional integration. These results bridge the gap between mobile-assisted language learning theory and classroom practice, offering both theoretical contributions to the understanding of Mobile-Assisted Language Learning (MALL) and pedagogical implications for integrating digital tools into EFL instruction. Duolingo and Quizlet, when appropriately guided, can transform vocabulary learning into an engaging, autonomous, and sustainable process for EFL learners.